2014
DOI: 10.1186/1472-6963-14-436
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of a cognitive behavioural therapy intervention for fear of falling: qualitative study of intervention development

Abstract: BackgroundFear of Falling (FoF) is commonly reported among older adults (up to 50%) and can impact negatively on physical and social activities, mood and quality of life. This paper explores the development, acceptability and feasibility of a cognitive behavioural therapy intervention (CBTi) for FoF.MethodsThe process evaluation of the CBTi development phase of an RCT (conducted in the UK) reported here, used ethnographic methods. Data included: interviews with patients and carers (n = 16), clinic staff (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Coupe et al [ 27 ] UK NPT Collaborative care for depression Yes Process evaluation Qualitative Retrospective Yes Yes Yes 9. Finch et al [ 28 ] UK NPT Cognitive behavioural therapy Systematic review [ 156 ] Yes Feasibility study Qualitative Prospective Yes Yes N/A 10. Furler et al [ 29 31 ] Australia NPT Diabetes management in primary care Yes Process evaluation Qualitative Prospective Yes Yes No 11.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coupe et al [ 27 ] UK NPT Collaborative care for depression Yes Process evaluation Qualitative Retrospective Yes Yes Yes 9. Finch et al [ 28 ] UK NPT Cognitive behavioural therapy Systematic review [ 156 ] Yes Feasibility study Qualitative Prospective Yes Yes N/A 10. Furler et al [ 29 31 ] Australia NPT Diabetes management in primary care Yes Process evaluation Qualitative Prospective Yes Yes No 11.…”
Section: Resultsmentioning
confidence: 99%
“…They used NPT in ‘identifying and describing the components and sub-components of the intervention’ to understand ‘the nuances associated with collective implementation’. The next most numerous group of studies focused on the implementation of diagnostic and therapeutic interventions ( n = 28, 25.9% [ 19 , 24 26 , 28 31 , 36 , 37 , 47 , 48 , 55 57 , 67 , 69 , 78 , 80 , 90 , 95 , 97 , 98 , 103 , 104 , 111 , 117 , 123 , 126 , 137 , 142 , 143 ]). For example, in the USA, Hoberg et al [ 98 ] examined the implementation of a new form of group therapy for people with mental health problems, while Leon et al [ 48 ] showed how provider initiated testing and counselling for HIV was successfully normalised in a South African setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a. The aim of this phase of the project was to develop a CBTi that could be delivered by HCAs (non-specialist, relatively low-paid staff), after training in basic CBT skills 18…”
Section: Resultsmentioning
confidence: 99%
“…On this basis, our research adds to previous research ndings, recognizing that fear of falling may be more important than previous falls in limiting the daily activities of older adults. Studies have shown that fear of falling can be alleviated by improving cognitive behavior and daily activities in older adults [34,35]. For older adults who have fear of falling, lifestyle changes are recommended to achieve effective intervention and reduce the incidence of falls [36].…”
Section: Discussionmentioning
confidence: 99%